Penegakan Hukum Terhadap Pelanggaran Pembangunan Di Sempadan Sungai Oleh Satuan Polisi Pamong Praja Provinsi Bali - I Wayan Suparta; Desak Ayu Putu Suciati (PARIKSA: Jurnal Hukum Agama Hindu, 2021)
As a tourist destination, environmental management is crucial, because it is also an effort to satisfy tourists' appetite so that the attractiveness of tourists to visit is getting higher. Apart from that, environmental management also provides significant benefits and contributions to the smooth and sustainable implementation of development programs, especially in the tourism sector in Bali. Therefore, maintaining a well-ordered environment is the obligation of all existing communities. However, there are still many people who are not aware of the importance of environmental management so that there are still many violations related to the environment in Bali. For example, such as Water Pollution by Tofu Waste in Tukad Badung Denpasar, water pollution in Tukad Badung here is mostly carried out by small-scale home businesses, such as Tofu Businesses, most of which do not have an AMDAL (Medium Environmental Impact Analysis) permission for reasons of low profit. In addition, the cause of environmental damage in Bali area is due to development on the riverbanks, such as the construction of unlicensed houses that have a negative impact on the surrounding environment because the construction of these houses will create household waste that will pollute river water. Then the first problem can be formulated. How is the law enforcement carried out by the Bali Provincial Civil Service Police Unit against the buildings in the River Border and secondly what are the obstacles faced by the Bali Provincial Civil Service Police Unit in enforcing the law against riverbank offenders. Finally, it can be concluded that there are many types local government actions in controlling spatial use in river border areas. The type of action in its implementation has been regulated in a standard operating procedure (SOP) and can be classified as public government action. As well as that the factors that influence legal action in controlling spatial use in the riverbank area consist of driving and inhibiting factors. The driving factor is the factor of the law, the factor of law enforcement and the factor of facilities and infrastructure. Meanwhile, the inhibiting factor in controlling the use of space in the river border area in Bali province is influenced by community factors.